Applying harm reduction to COVID-19 prevention: The influence of moderation messages and risk infographics. Issue 2 (February 2022) - Kemp, Deena; King, Andy J.; Upshaw, Sean J.; Mackert, Mike; Jensen, Jakob D.
Highlights: Recruited a quota sample, approximating race, gender, and high-school attainment trends of adults in the United States. Depicting high-risk behaviors, like attending a concert, increased freedom threat regardless of harm reduction guidelines. Harm reduction reduced freedom threat, but only when low-risk behaviors, like going camping, were emphasized. Harm reduction increased prevention intentions among risk-willing individuals when high-risk behaviors were salient. Abstract: Objective: We propose that harm reduction messages advocating moderation versus abstinence from social interaction will be seen as less threatening and increase intentions to follow COVID-19 guidelines. We also examine two important moderators: the influence of risk framing and willingness to risk infection. Method: A 2 × 2 between-participants, randomized experiment ( N = 476) varied infographics portraying low-risk behaviors, like going camping, versus high-risk behaviors, like attending a concert, followed by either moderation or abstinence guidelines. Participants in two additional control groups saw an infographic displaying either a full range of risk behaviors or behaviors that pose no risk, each followed by generic guidelines. Results: Regression analyses show moderation messages are less freedom-threatening only when presenting low-risk behaviors. Persons more willing to risk infection found all messages more freedom-threatening; however, for these individuals, moderation messages increased behavioral intentions when risks were presented as high. Conclusion: This study suggests harm reduction may be applied effectively in a pandemic, where the behavior of risk-tolerant individuals, at a population level, could have suboptimal effects on curbing virus transmission. Practice implications: Health educators should communicate harm reduction with certain populations but also test to ensure messaging, including visuals communicating relative risks, are received as intended.